Cost-Effectiveness of Treatments after Closed Extraarticular Distal Radius Fractures in Older Adults from the WRIST Clinical Trial. Issue 2 (24th November 2020) - Yoon, Alfred P.; Shauver, Melissa J.; Hutton, David W.; Chung, Kevin C.; ,
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: This study performs an economic analysis of volar locking plate, external fixation, percutaneous pinning, or casting in elderly patients with closed distal radius fractures. Methods: This is a secondary analysis of the Wrist and Radius Injury Surgical Trial, a randomized, multicenter, international clinical trial with a parallel nonoperative casted group of patients older than 60 years with surgically indicated, extraarticular closed distal radius fractures. Thirty-Six-Item Short-Form Health Survey–converted utilities and total costs from Medicare were used to calculate quality-adjusted life-years and incremental cost-effectiveness ratio. Results: Casted patients were self-selected and older ( p < 0.001) than the randomized surgical cohorts, but otherwise similar in sociodemographic characteristics. Quality-adjusted life-years for percutaneous pinning were highest at 9.17 and external fixation lowest at 8.81. Total costs expended were $16, 354 for volar locking plates, $16, 012 for external fixation, $11, 329 for percutaneous pinning, and $6837 for casting. The incremental cost-effectiveness ratios for volar locking plates and external fixation were dominated by percutaneous pinning and casting. The ratio for percutaneous pinning compared to casting was $28, 717. Probabilistic sensitivity analysis revealed a 10, 5, 53, and 32 percent chance of volar locking plate, external fixation, percutaneous pinning, and casting, respectively, being cost-effective at the willingness-to-pay threshold of $100, 000 per quality-adjusted life-year. Conclusions: Casting is the most cost-effective treatment modality in the elderly with closed extraarticular distal radius fractures and should be considered before surgery. In unstable closed fractures, percutaneous pinning, which is the most cost-effective surgical intervention, may be considered before volar locking plates or external fixation.